Inflammatory indices—Systemic Immune-Inflammation Index (SII) and Systemic Inflammatory Response Index (SIRI)—during Pregnancy and Associations with Gestational Diabetes Mellitus - Zhang D; Zeng Y; Sun B; Li W; Liu W; Gao H; Zhu Y; Li H; Chen Q (Dove Medical Press, 2024)
Danwei Zhang,1 Yating Zeng,1 Bin Sun,2 Wei Li,2 Wenjuan Liu,2 Haiyan Gao,2 Yibing Zhu,2 Haibo Li,2,* Qiang Chen1,* 1Department of Cardiac Surgery, Fujian Children's Hospital (Fujian Branch of Shanghai Children's Medical Center), College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, People's Republic of China; 2Division of Birth Cohort Study, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiang Chen, Department of Cardiac Surgery, Fujian Children's Hospital (Fujian Branch of Shanghai Children's Medical Center), College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, No. 966 Hengyu Road, Jinan District, Fuzhou, 350014, People's Republic of China, Email chenqiang2228@163.com Haibo Li, Division of Birth Cohort Study, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, No. 18 Daoshan Road, Gulou District, Fuzhou, 350001, People's Republic of China, Email haiboli89@163.comPurpose: Gestational diabetes mellitus (GDM) is a prevalent complication during pregnancy. This study aimed to explore the associations between inflammatory indices during pregnancy and the development of GDM.Methods: Data from the Fujian Birth Cohort Study between March 2019 and December 2022 were used. Participants who delivered a live-born singleton were included and categorized into GDM and non-GDM groups. Two inflammatory indices, the systemic immune-inflammation index (SII) and systemic inflammatory response index (SIRI), were calculated for each trimester of pregnancy via hematological parameters from complete blood count tests. The distributions of inflammatory indicators across trimesters were compared between the GDM and non-GDM groups. Additionally, multivariable logistic regression models were employed to investigate the associations between inflammatory indices and the incidence of GDM.Results: A total of 17297 participants were included, 21.2% of whom were diagnosed with GDM. In the first trimester, the median SIIs for the GDM and non-GDM groups were 817.7× 109/L and 756.9× 109/L, respectively, whereas the median SIRIs were 1.6× 109/L and 1.5× 109/L, respectively. In both groups, the SII increased to its peak in the second trimester before declining, whereas the SIRI progressively increased throughout pregnancy. The SII and SIRI were greater in the GDM group than in the non-GDM group during the first two trimesters but lower in the third trimester. Nonlinear positive associations between first-trimester SII and SIRI levels and GDM were observed, with extreme quartile odds ratios of 1.32 (95% CI: 1.19, 1.48) and 1.39 (95% CI: 1.24, 1.55), respectively.Conclusion: The SII and SIRI increased and reached their peak values in the second and third trimesters of pregnancy, respectively. Elevated levels of the SII and SIRI in early pregnancy were linked to an increased risk of GDM, suggesting their potential utility as screening tools for GDM.Keywords: gestational diabetes mellitus, GDM, systemic immune-inflammation index, SII, systemic inflammatory response index, SIRI